Biological behaviour of 90Y-labeled micro- and nanoparticles in tumor-bearing mice - Vukadinović, Aleksandar; Knežević, Nikola; Janković, Drina; Radović, Magdalena; Perić, Marko; Mirković, Marija; Milanović, Zorana; Stanković, Dragana; Vranješ Đurić, Sanja; Prijović, Željko; Erić, Slavica (Archives of Pharmacy, 2022)
Radioisotopes such as 90Y that emit beta-particles are well known to be suitable for use in tumor therapy. In addition, the delivery of a variety of therapeutics using nanoparticles has become a large field of research in recent years. This study examined the biological behavior of three different micro- and nanoparticle formulations that carry the therapeutic 90Y radioisotope. The first formulation was 90Y-labeled citrate-coated superparamagnetic iron-oxide nanoparticles (90Y-CA-SPIONs), the second was mesoporous silica-coated superparamagnetic iron-oxide nanoparticles (90Y-Mag-MSN), and third formulation was 90Y-labelled albumin microspheres (90Y-AMS). All three formulations are shown to be stable over the relevant period of radioisotope decay. The sizes of particles were 22nm, 386nm, and 38µm for 90Y-CA-SPIONs, 90Y-Mag-MSN, and 90Y-AMS, respectively. The biodistribution studies were done using tumor-bearing BALB/c mice. The results showed that, after the i.v. injection, the biodistribution was dependent on particle sizes. Thus, smaller particles (90Y-CA-SPIONs and 90Y-Mag-MSN) were taken up mainly by the liver and spleen (>90%ID), and larger particles (90Y-AMS) were taken up entirely by the lungs. None of the formulations had a tumor uptake of more than 1%ID. After the direct intratumoral injection, all three formulations have shown to be stable, and radioactivity remained only in tumors during the four days of follow-up. This study confirms the delivery of nanoparticles to solid tumors after i.v. injection is a challenge due to the low uptake by tumor tissue. Nevertheless, all three examined materials have shown to be suitable for a direct intratumoral application, and 90Y-AMS is suitable for radioembolization (SIRT) procedures.